Forming state through land reform policy: the dynamics of baldío allocation in peripheral Colombia (2017)
This paper analyses land policy when the state lacks the monopoly of legitimate violence (MLV) through a territory. I use historical data for Colombia to empirically assess the dynamics through which the central state allocates land in such a scenario. I argue that colonization processes directed towards peripheral areas with lack of the MLV induces the state to attempt building capacity using land policy. Public goods nevertheless do not follow. I use an instrumental variable strategy in order to examine these hypotheses. Results show that rural migration towards the peripheral areas accounts for 42.01% of the total number and 68.55% of the total hectares of public land allocations. Allocations however account for only the 7.89% of the number police-men and the 6% of the number of policemen per inhabitant in these regions. Moreover, both their total and per hectare effect on police presence is much higher in the integrated zones than in the peripheral ones.